2023
DOI: 10.21203/rs.3.rs-2565156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrogen-Enriched Organic fertilizer (NEO) elevates nitrification rates shortly after application but has no lasting effect on nitrification in agricultural soils

Abstract: In times of growing population, scarcity of arable land, and increasing use of synthetic nitrogen, new sustainable fertilizers are needed to enhance the resilience of global agri-food systems. Nitrogen-Enriched Organic fertilizer (NEO) is an example of a potentially sustainable fertilizer. Dinitrogen (N2) is captured from the air by a plasma process and mixed as nitrate (NO3−) and nitrite (NO2−) with animal slurries or other liquid organic fertilizers. This process strongly acidifies the slurry, which, togethe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…We found that the plasma induction process increased the nitrate-N content of the pig slurry; the higher content of inorganic N combined with the C in the pig slurry is likely to be responsible for the higher N 2 O emissions (Shurpali et al 2016;Li et al 2022) from TPS compared to PS. Mousavi et al (2023) found that the nitrification potential of plasma-treated pig slurry was higher than that of other fertilisers due to its higher volatile organic C content, which reduces ammonia immobilisation, and so may also explain the higher N 2 O emissions from TPS. Denitrification is highly influenced by pH, with denitrification being slowed or even inhibited at lower pH levels (Liu et al 2010;Olaya-Abril et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…We found that the plasma induction process increased the nitrate-N content of the pig slurry; the higher content of inorganic N combined with the C in the pig slurry is likely to be responsible for the higher N 2 O emissions (Shurpali et al 2016;Li et al 2022) from TPS compared to PS. Mousavi et al (2023) found that the nitrification potential of plasma-treated pig slurry was higher than that of other fertilisers due to its higher volatile organic C content, which reduces ammonia immobilisation, and so may also explain the higher N 2 O emissions from TPS. Denitrification is highly influenced by pH, with denitrification being slowed or even inhibited at lower pH levels (Liu et al 2010;Olaya-Abril et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…This difference in nitrogen absorption timing may help explain why MiNEO120 consistently resulted in higher wheat yields than barley in most of our trials. Another contributing factor could be the high nitrification potential of NEO, which leads to greater availability of plant-accessible nitrate over a concentrated period of 3-4 days following application [18]. This rapid release of nitrate may particularly benefit wheat [31,32].…”
Section: Neo At Three Leaf Stagementioning
confidence: 99%
“…Since NEO is a novel product, assessing its impact on plant yield and its effectiveness compared to conventional fertilizers, e.g., mineral fertilizers, cattle slurry, etc., is essential before considering its commercialization. Thus, to accomplish this, we at Inland Norway University of Applied Sciences (INN) conducted comprehensive trials to document and compare the effects of NEO on soil health [17,18] and plant yields in the growing chamber [19] and cereal and grass fields at different locations in Norway over three years (2020 to 2022).…”
Section: Introductionmentioning
confidence: 99%